Should banks be narrowed? - Biagio Bossone (Levy Economics Institute of Bard College, 2002)
Over the past 70 years, a proposal to narrow the scope of banks has emerged more and more frequently in financial debates and research. Narrow banking would prevent deposit-issuing banks from lending to the private sector and restrict nonbank intermediaries from funding investments with demand deposits. Proponents of narrow banking defend it as a step toward greater financial stability and efficiency. This study reviews the literature on the subject, contrasts the concept of narrow banking with contemporary banking theories, and evaluates the potential effects of narrow banking on finance and the real economy. The study also delineates an empirical exercise to estimate the costs of bank narrowness and draws policy conclusions based on those estimates.
Keywords: 330